White Matter Injury in Preterm Infants: Pathogenesis and Potential Therapy From the Aspect of the Gut–Brain Axis - He, Yu; Zhang, Yuni; Li, Fang; Shi, Yuan (Frontiers in Neuroscience, 2022)
Very preterm infants who survive are at high risk of white matter injury (WMI). With a greater understanding of the pathogenesis of WMI, the gut microbiota has recently drawn increasing attention in this field. This review tries to clarify the possible mechanisms behind the communication of the gut bacteria and the immature brain via the gut–brain axis. The gut microbiota releases signals, such as microbial metabolites. These metabolites regulate inflammatory and immune responses characterized by microglial activation, which ultimately impact the differentiation of pre-myelinating oligodendrocytes (pre-OLs) and lead to WMI. Moreover, probiotics and prebiotics emerge as a promising therapy to improve the neurodevelopmental outcome. However, future studies are required to clarify the function of these above products and the optimal time for their administration within a larger population. Based on the existing evidence, it is still too early to recommend probiotics and prebiotics as effective treatments for WMI.